(untitled) (TEST Ticontre. Theory Text Translation, 2022)
Focusing on Jennifer Egan’s Manhattan Beach, the article analyzes the role of the sea and water in general – both as metaphors and physical elements - in defining a deep movement that allows the writer to tackle many stereotypical representations of the Ameri-can civil society and the military environment during the Thirties and Forties. In following the link between the protagonist’s female gaze and the constant presence of the sea as a constitutive element of the novel, we’ll see, in thematic terms, how this work offers a new perspective to look at the New York City during wartime as well as to the maritime literary tradition itself; while, in theoretical terms, it presents the reader with a frictional effect with respect to the category of historical novel and provides instead a potential counter-history.